The Organizational Justice of the Public School Principals in Palestine from their Teachers' Point of View - Zeiad Barakat (Sultan Qaboos University, 2016)
This study aimed to determine the extent of organizing justice within governmental schools' principals in Palestine from school teacher's point of view. Some demographic variables were used such as gender, major, qualification and experience. A questionnaire that consisted of 33 items was developed. The questionnaire consisted of three domains: organizational justice, procedural justice and interactive justice. A stratified random sample was drawn and consisted of 284 teachers. The results showed that teachers evaluated their principals as having high organizational justice on the sub- domains and the total. The results showed differences due to years of experience on the distributing justice domain and the total in favor of more experienced teachers. The results showed no significant difference in the domains of procedural and interactive justices. The results also showed no significant differences in organizational justice due to: gender, major and qualification. These results were discussed and recommendations were suggested.